2017
DOI: 10.9787/pbb.2017.5.3.213
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity and Population Structure of Mongolian Wheat Based on SSR Markers: Implications for Conservation and Management

Abstract: Production of spring wheat, the major crop in Mongolia, accounts for 98% of the cultivated area. Understanding genetic variability in existing gene bank accessions is critical for collection, conservation and use of wheat germplasms. To determine genetic diversity and population structure among a representative collection of Mongolian local wheat cultivars and lines, 200 wheat accessions were analyzed with 15 SSR markers distributed throughout the wheat genome. A total of 85 alleles were detected, with three t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 33 publications
4
4
0
Order By: Relevance
“…An alternative explanation is that the higher proportion of rare alleles in the D genome compared to the A and B genomes may have been more susceptible to genetic drift during modern cultivar development, creating a recent genetic bottleneck in the D genome [ 66 ]. The relative contributions of the different genomes to SNP diversity as obtained using GBS-derived SNP markers are also in agreement with the results of past studies performed on hexaploid wheat using DArT markers [ 14 , 67 , 68 ] and SSR markers [ 34 , 38 , 41 , 69 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…An alternative explanation is that the higher proportion of rare alleles in the D genome compared to the A and B genomes may have been more susceptible to genetic drift during modern cultivar development, creating a recent genetic bottleneck in the D genome [ 66 ]. The relative contributions of the different genomes to SNP diversity as obtained using GBS-derived SNP markers are also in agreement with the results of past studies performed on hexaploid wheat using DArT markers [ 14 , 67 , 68 ] and SSR markers [ 34 , 38 , 41 , 69 ].…”
Section: Discussionsupporting
confidence: 89%
“…All the three methods used (population structure, UPGMA clustering, and PCA) consistently led to this grouping. The consistency of grouping using these methods has also been observed in earlier studies [ 32 34 ]. The differentiation of the population into different subpopulations by fastSTRUCTURE is based on frequencies of relatedness of the genotypes to each of the subpopulations as hypothesized [ 14 , 35 , 36 ].…”
Section: Discussionsupporting
confidence: 79%
“…Sourour et al [16] has shown important phenotypic diversity of the Tunisian germplasm estimated to 0.77 using Shannon–Weaver indices. Several molecular markers techniques were used to assess the genetic diversity in wheat including RFLP, RAPD, ISSR, AFLP, EST–SSR [17], DArT, and SNP [18,19]. A significant genetic difference using SSR markers was detected between landraces of durum wheat originated from Morocco and Syria using the Bayesian method and the Eigen analysis [20].…”
Section: Introductionmentioning
confidence: 99%
“…A principle coordinate analysis (PCoA) was conducted using the software GenAlEx V6.503 [ 53 , 54 ]. The population structure of 384 peanut accessions was evaluated by Structure v2.3.4 software ( ) under the admixture model.…”
Section: Methodsmentioning
confidence: 99%